Thursday

March 26, 2015

March 26, 2015

Posted by **Candy** on Wednesday, August 26, 2009 at 5:35pm.

- math -
**Ms. Sue**, Wednesday, August 26, 2009 at 5:49pm12n=9(n+10)

12n = 9n + 90

12n - 9n = 9n - 9n + 90

3n = 90

n = ?

- math -
**DrBob222**, Wednesday, August 26, 2009 at 5:51pm12n=9(n+10)

**remove parentheses**

12n = 9n+90

Move unknown (n) to the same side by subtracting 9n from both sides.

12n-9n = 9n-9n+90

combine terms.

3n=90

divide both sides by 3.

3n/3 = 90/3

n=?

**Answer this Question**

**Related Questions**

Math - Solve and check each equation 1a. 12n=36 n=3 1b. n-5=8 n=13

algebra - What inequality represents the sentence the product of a number and 12...

Algebra - 1. Find the degree of the monomial 6p^3 q^2. A) 2 B) 3**** C) 5 D) 6 ...

algebra 2 - 1. 5x+2>3x+10 =x>4 2. 8+2x< or equal too 6x-20 x> or ...

Quick math help - I need help with solving these problems. When I checked it it ...

MATH - I NEED TO SOLVE FOR Y AND X im getting rele confused on this. ok here is ...

calculus - find the resultant of each pair of forces acting on an object a) ...

Algebra - 5(2n + 4) - 3(4n - 6) = 2(20 - n) I solved this equation and this is ...

algebra - What is the value of n in the equation 12n + 8 = 11? Please submit ...

math - determine the equation of the line in y=mx+b form that passes through 1...